Effect of Postural Control Demands on Early Visual Evoked Potentials during a Subjective Visual Vertical Perception Task in Adolescents with Idiopathic Scoliosis - Chang, Yi-Tzu; Meng, Ling-Fu; Chang, Chun-Ju; Lai, Po-Liang; Lung, Chi-Wen; Chern, Jen-Suh (Frontiers in Human Neuroscience, 2017)
Subjective visual vertical (SVV) judgment and standing stability were separately investigated among patients with adolescent idiopathic scoliosis (AIS). Although one study has investigated the central mechanism of stability control in the AIS population, the relationships between SVV, decreased standing stability, and AIS have never been investigated. Through event-related potentials (ERPs), the present study examined the effect of postural control demands (PDs) on AIS central mechanisms related to SVV judgment and standing stability to elucidate the time-serial stability control process. Thirteen AIS subjects (AIS group) and thirteen age-matched adolescents (control group) aged 12–18 years were recruited. Each subject had to complete an SVV task (i.e., the modified rod-and-frame [mRAF] test) as a stimulus, with online electroencephalogram recording being performed in the following three standing postures: feet shoulder-width apart standing, feet together standing, and tandem standing. The behavioral performance in terms of postural stability (center of pressure excursion), SVV (accuracy and reaction time), and mRAF-locked ERPs (mean amplitude and peak latency of the P1, N1, and P2 components) was then compared between the AIS and control groups. In the behavioral domain, the results revealed that only the AIS group demonstrated a significantly accelerated SVV reaction time as the PDs increased. In the cerebral domain, significantly larger P2 mean amplitudes were observed during both feet shoulder-width-apart standing and feet together standing postures compared with during tandem standing. No group differences were noted in the cerebral domain. The results indicated that (1) during the dual-task paradigm, a differential behavioral strategy of accelerated SVV reaction time was observed in the AIS group only when the PDs increased and (2) the decrease in P2 mean amplitudes with the increase in the PD levels might be direct evidence of the competition for central processing attentional resources under the dual-task postural control paradigm.